Recovery of Ruthenium Via Zinc in the Presence of Accelerator - AKTAŞ, SERDAR (SPRINGER INDIA, 2018)
In this study, the recovery of ruthenium from spent bath solutions via cementation reaction with zinc powder was investigated. Studied parameters included the quantity of zinc, reaction temperature, reaction time and sodium chloride additions to understand their effects on the reaction. Tests were performed in a temperature controlled water-bath with temperatures between 20 and 70 A degrees C at atmospheric pressure. Furthermore, in order to determine activation energy of cementation reaction, several mathematical kinetic models were used and the activation energy, which was calculated from best fit, was found to be 12.48 kJ/mol. Addition of sodium chloride to the solution greatly accelerated the cementation reaction, in that, more the addition of sodium chloride, the better was the precipitation efficiency. In the absence of sodium chloride at 25 A degrees C a percentage of ruthenium recovery was below 75% whereas 1000 mg sodium chloride addition at 65 A degrees C ensured a percentage of ruthenium recovery more than 95%. This corresponded to more than about 28% increase.
Keywords: Ruthenium; Zinc; Cementation; Recovery; Spent bath solutions; CHLORIDE SOLUTIONS; SILVER RECOVERY; CEMENTATION; SEPARATION; EXTRACTION; BEHAVIOR; METALS; POWDER; COPPER; IONS